PETRA CHRISTIAN UNIVERSITY STUDENT EXECUTIVE BOARD (BEM) PROJECT MANAGEMENT SYSTEM - ., Yulia; Rahardjo, Arlinah Imam; ., Suryani (Institute of Research and Community Outreach - Petra Christian University, 2012)
Petra Christian University Student Executive Board (BEM) needs an administrative and project management system that can help managing the activities. This Board was having a problem of coordination on managing the activities they have. The tight schedule of each member of the executive staffs who comes from different departments has created this problem. To answer the above problem, an administrative and project management system is developed to help PCU BEM managing each of their activities. The scope of the system covers access privileges, job divisions and task assignments, proposal creation and budgeting arrangements of the implementation of each activity. The application is developed as a web-based system using Macromedia Dreamweaver MX 2004, PHP and JavaScript programming language and MySQL database system. The system testing concludes that the application is able to support the performances of the BEM executive staff members in managing their activities. The detailed job divisions let the implementation process of each activity be easily viewed by each executive staff member.